Рекультивація фітоценозів техногенних екосистем м. Борислав - Цайтлер, М. Й. (Видавництво Львівської політехніки, 2012)
Исследовано способы рекультивации фитоценозов техногенных экосистем Бориславского нефтяного и озокеритного месторождений. Изучены механизмы природного заростания этих територий. Заложено модельные площадки рекультивации, на которых высажывали растения. Проведено оценку устойчивости видов растений к техногенным субстратам та отримано дані про їх придатність для фіторекультивації. Розроблено оптимальні моделі рекультивації. Has been investigated ways phytocenosical recultivation of technogenic ecosystem of Boryslav oil and ozokerite deposits. Have been created the model areas of cultivation, on which plants seeded. Has been done estimation of the stability of plant species to technogenic substrates and obtained data on their suitability for phyto-recultivation. Has been elaborated an optimal models of recultivation.
Рекультивация фитоценозов техногенных экосистем г. Борислава
Рhytocenosical recultivation of technogenic ecosystem of Boryslav